1993
DOI: 10.1007/bf00602836
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous embolization of dural caroticocavernous fistulae: technical considerations

Abstract: Sixteen patients with symptomatic dural caroticocavernous fistulae were treated by transvenous embolization, via the jugular vein and inferior petrosal sinus. The fistula was occluded by thrombogenic coils. Complete resolution of symptoms and signs was achieved in 14 patients, and complete angiographic resolution was also obtained in 14 patients. Failures to achieve angiographic cure were attributed to failure to reach the fistula within the cavernous sinus precisely. Factors which make placement of the cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…That is, all the results for the patients t reated with the transarterial approach only were classified as failures, while for 61% of the patients, t reated with a transvenous approach, the re s u l t s w e re successful. This information agrees with the experiences of some authors who advocate the transvenous approach as the method of choice to achieve clinical and angiographic cure for DAV M s of the cavernous sinus 19,20,22,24 .…”
Section: Cavernous Sinussupporting
confidence: 88%
“…That is, all the results for the patients t reated with the transarterial approach only were classified as failures, while for 61% of the patients, t reated with a transvenous approach, the re s u l t s w e re successful. This information agrees with the experiences of some authors who advocate the transvenous approach as the method of choice to achieve clinical and angiographic cure for DAV M s of the cavernous sinus 19,20,22,24 .…”
Section: Cavernous Sinussupporting
confidence: 88%
“…Debrun et al 10 reported a 20% incidence of transient oculomotor nerve palsy, which is usually attributable to sixth cranial nerve dysfunction. 11 For DCCFs that are not successfully treated with ICA preservation by using a detachable balloon, transarterial GDC embolization is an alternative treatment. In 1992, Guglielmi et al 12 successfully treated DCCFs by transvenous GDC embolization, and there have been several subsequent reports of transarterial GDC embolization of DCCFs with favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of venous approaches have been reported: the inferior petrosal sinus (IPS) route was the first established and most commonly used [4][5][6] , especially for venous hormone sampling 2,3 . When the ophthalmic vein [7][8][9][10][11][12][13][14][15][16][17][18][19][20] , superior petrosal sinus (SPS) 21 and pterigoid plexus (PP) 22 are involved in venous drainages of CCFs, each venous channel may become an appropriate access route.…”
Section: Transvenous Approaches To the Csmentioning
confidence: 99%
“…Yamashita et al 6 reported complications occurring in 7 of 16 patients with TVE. One was epidural extravasation from perforation of the inferior petrosal sinus.…”
Section: Indications and Contraindications Of Each Proceduresmentioning
confidence: 99%